God’s return in a secular age - Oviedo Torró, Lluís (Razón y fe, 2019)
We wonder to what extent we can speak of a return of God in a very secularized cultural environment. There are signs, some of them very explicit, that should be taken into account when answering this question. There are three main scenarios: references to God’s return in a sociological key, together with indications about the therapeutic value of faith; the lively atmosphere of scientists who convert, and the dialogue between science and religion; and the discussions promoted by the so-called ‘new atheism’.